Medium-term oncological efficacy and patient-reported outcomes after focal high-intensity focused ultrasound: the FOXPRO trial - Westhoff, Niklas Christian; Ernst, Ramona; Kowalewski, Karl-Friedrich; Derigs, Fabian; Neuberger, Manuel; Nörenberg, Dominik; Popovic, Zoran V.; Ritter, Manuel; Michel, Maurice Stephan; Hardenberg, Jost von (European urology focus, 2023)
Background - Multiparametric magnetic resonance imaging (mpMRI)/transrectal ultrasound (TRUS) fusion-guided high-intensity focused ultrasound (HIFU) is a focal treatment option for MRI-visible localized prostate cancer (PCa). High-quality evidence regarding the clinical efficacy remains limited. - Objective - To assess medium-term oncological efficacy along with patient-reported outcome measures (PROMs). - Design, setting, and participants - This prospective single-center cohort study was performed from 2014 to 2020. Patients with primary International Society of Urological Pathologists (ISUP) grade group (GG) ≤2 by combined MRI/TRUS fusion and systematic prostate biopsy and prostate-specific antigen (PSA) <10 ng/ml were included. - Intervention - MRI/TRUS fusion-guided focal HIFU therapy. - Outcome measurements and statistical analysis - The primary outcome was the cancer-free rate of the HIFU-treated lesion by biopsy after 1 yr. Secondary endpoints included salvage treatment-free survival (STFS), metastasis-free survival (MFS), overall survival (OS), and PROMs according to International Consortium for Health Outcomes Measurement recommendations. - Results and limitations - Fifty patients were included (median [range] age 68 [48-80] yr; median PSA 6.5 [1.2-9.9] ng/ml; GG 1 54% [n = 27], and GG 2 46% [n = 23]). The median (range) PSA decrease from baseline to 12 mo was 51% (35.9-72.7%). In total, 37/50 patients (74%) underwent a 1-yr biopsy. PCa was detected in 23 patients (46%; GG 1 20% [n = 10]; GG >1 26% [n = 13]; infield 40% [n = 20]). At a median follow-up of 42 (13-73) mo, PCa was detected in 30 men (60%). Among all patients, 19 (38%) underwent salvage treatments (median [95% confidence interval] STFS 53 [44.3-61.7] mo). MFS and OS were 100% and 98%, respectively. The Expanded Prostate Cancer Index Composite-26 sexual domain decreased by 20.8 points (p = 0.372). - Conclusions - MRI/TRUS-guided focal HIFU therapy results in complete cancer ablation in only half of the treated patients after 1 yr, with further recurrences at medium-term follow-up. A decline of potency occurs in a subset of patients. - Patient summary - Focal image-guided high-intensity focused ultrasound therapy controls cancer in one of two patients. Its impact on urinary continence and erectile function is low.
Online verfügbar: 4. November 2022, Artikelversion: 29. März 2023
Gesehen am 18.07.2024